2016
DOI: 10.20897/lectito.201604
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing learners’ problem solving performance in mathematics: A cognitive load perspective

Abstract: This paper reports on a pilot study that investigated the effect of implementing a context-based problem solving instruction (CBPSI) to enhance the problem solving performance of high school mathematics learners. Primarily, the pilot study aimed: (1) to evaluate the efficiency of data collection instruments; and, (2) to test the efficacy of CBPSI in relation to learners' problem solving performance. In this paper CBPSI refers to a teaching approach in which everyday problem solving knowledge and practices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Lecturers should do the same when they provide feedback on assignments in the form of a memorandum. In so doing, they can demonstrate to students what constitutes good practice in solving a problem as research has shown that people learn by copying the actions of others [43].…”
Section: Discussionmentioning
confidence: 99%
“…Lecturers should do the same when they provide feedback on assignments in the form of a memorandum. In so doing, they can demonstrate to students what constitutes good practice in solving a problem as research has shown that people learn by copying the actions of others [43].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, guiding and encouraging learners to invest more time and effort in defining the problem and finding solutions allows them to reflect on the quality of their own representations and solutions (Law et al, 2021). Various studies (Azimah et al, 2020;Dhlamini, 2016;Zahara et al, 2020) also stated that CLT-based education could effectively develop and strengthen learners' problem-solving skills and schemas and their learnings, as demonstrated by research focusing on problem-solving first approach (Likourezos & Kalyuga, 2017), goal-free tasks (Purnama & Retnowati, 2020), worked examples (Sentz & Stefaniak, 2019), self-explanations (Joo et al, 2020), imagination (Leopold & Mayer, 2015) and guided learning (Simamora et al, 2019).…”
Section: Challenges Encountered In Problem-solving Steps and Ways To ...mentioning
confidence: 99%
“…Evidence from preliminary studies further demonstrates that domain prior knowledge may play a role in the interaction between task difficulty and instructional strategy (Dhlamini, 2016;Orvis, Horn, & Belanish, 2008). Orvis et al (2008) examined the role of instructional strategy in video-game based learning.…”
Section: Task Difficultymentioning
confidence: 99%